Assessing Short‐Term Impacts of Management Practices on N2O Emissions From Diverse Mediterranean Agricultural Ecosystems Using a Biogeochemical Model. Issue 5 (11th May 2018) - Deng, Jia; Li, Changsheng; Burger, Martin; Horwath, William R.; Smart, David; Six, Johan; Guo, Lei; Salas, William; Frolking, Steve
Abstract: Croplands are important sources of nitrous oxide (N2 O) emissions. The lack of both long‐term field measurements and reliable methods for extrapolating these measurements has resulted in a large uncertainty in quantifying and mitigating N2 O emissions from croplands. This is especially relevant in regions where cropping systems and farming management practices (FMPs) are diverse. In this study, a process‐based biogeochemical model, DeNitrification‐DeComposition (DNDC), was tested against N2 O measurements from five cropping systems (alfalfa, wheat, lettuce, vineyards, and almond orchards) representing diverse environmental conditions and FMPs. The model tests indicated that DNDC was capable of predicting seasonal and annual total N2 O emissions from these cropping systems, and the model's performance was better than the Intergovernmental Panel on Climate Change emission factor approach. DNDC also captured the impacts on N2 O emissions of nitrogen fertilization for wheat and lettuce, of stand age for alfalfa, as well as the spatial variability of N2 O fluxes in vineyards and orchards. DNDC overestimated N2 O fluxes following some heavy rainfall events. To reduce the biases of simulating N2 O fluxes following heavy rainfall, studies should focus on clarifying mechanisms controlling impacts of environmental factors on denitrification. DNDC was then applied to assess the impacts on N2 O emissions of FMPs, including tillage, fertilization, irrigation, and management of cover crops. The practices that can mitigate N2 O emissions include reduced or no tillage, reduced N application rates, low‐volume irrigation, and cultivation of nonleguminous cover crops. This study demonstrates the necessity and potential of utilizing process‐based models to quantify N2 O emissions from regions with highly diverse cropping systems. Key Points: We tested the capability of a process‐based model (DNDC) for predicting N2 O emissions from various cropping systems N2 O mitigation efficiencies of management practices have been assessed for the investigated cropping systems DNDC performed better than the emission factor approach in quantifying N2 O emission from regions with diverse cropping systems